2017
DOI: 10.1016/j.ejmech.2017.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel antitumor nitric oxide-donating β -elemene hybrids through inhibiting the PI3K/Akt pathway

Abstract: A series of novel furoxan-based NO-donating β-elemene hybrids were designed and synthesized to improve the anticancer efficacy of natural β-elemene. The bioassay results indicated that all of the target compounds exhibited significantly improved antiproliferative activities against three cancer cell lines (SGC-7901, HeLa and U87) compared to parent compound β-elemene. Interestingly, these compounds displayed excellent sensitivity to U87 cells with IC50 values ranging from 173 to 2 nM. Moreover, most compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Researchers have accumulated data on the biological activities of non-curcuminoids and revealed that these components of turmeric have similar dynamic potential as curcuminoids and exhibits non-hepatotoxic, non-mutagenic, non-carcinogenic efficiency with the fewest side effects [16]. This review pioneers to collaborate all the foregoing extensive anticancer studies on some major non-curcuminoids (Figure 2) such as ar–turmerone, β–elemene, δ-elemene, furanodiene, furanodienone, curcumol, cyclocurcumin, calebin A, germacrone, bisacurone and curdione [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,…”
Section: Non-curcuminoids As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have accumulated data on the biological activities of non-curcuminoids and revealed that these components of turmeric have similar dynamic potential as curcuminoids and exhibits non-hepatotoxic, non-mutagenic, non-carcinogenic efficiency with the fewest side effects [16]. This review pioneers to collaborate all the foregoing extensive anticancer studies on some major non-curcuminoids (Figure 2) such as ar–turmerone, β–elemene, δ-elemene, furanodiene, furanodienone, curcumol, cyclocurcumin, calebin A, germacrone, bisacurone and curdione [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,…”
Section: Non-curcuminoids As Anticancer Agentsmentioning
confidence: 99%
“…Hence, reducing the tumor weight and volume in nude mice, MMP in HCCSMMC-7721 cells, and brought cell cycle arrest at the G2/M phase [66]. Chen et al studied that novel furoxan-based NO-donating β-elemene hybrids are promising anticancer agent [67]. Their studies also demonstrated isopropanolamine derivatives of β-elemene are effective chemotherapeutic agents [68].…”
Section: Non-curcuminoids As Anticancer Agentsmentioning
confidence: 99%
“…In addition, the regulation of biochemical substances (SOD, MDA, NO, and LDH) in HUVECs treated with hydrogen peroxide is better than that of the positive control vitamin [148], and so, β-elemene may be a potential treatment to effectively resist oxidative stress associated with cardiovascular disease. β-Elemene and some derivatives produce high levels of NO in vitro, and its antitumor activity in U87 cells was significantly attenuated by NO scavengers (hemoglobin or carboxyl-PTIO), and blocking activation of the PI3K/Akt pathway induced G2 arrest of the cell cycle and apoptosis in U87 cells, inhibiting tumor growth [149,150].…”
Section: β-Elemenementioning
confidence: 99%
“…Further in vivo studies showed the anticancer activity of 11a with a tumor inhibitory ratio (TIR) of 64.8%, which was higher than that of β-elemene (TIR, 49.6%) at a dose of 60 mg/kg. 92 IIi IIi, 13,14-bis(cis-3,5-dimethyl-1-piperazinyl)-β-elemene, is a novel β-elemene derivative with a cis-2,6-dimethylpiperazine substitution and is a potent agent for inhibiting the proliferation of 15 human tumor cell lines, with an average IC 50 of 3.44 µM, and the secondary amino group may contribute to this effect. IIi also exhibited strong cytotoxicity in two MDR cell lines (K562/A02 and MCF-7/Adr), with an average resistance factor (RF) of 1.66.…”
Section: Amentioning
confidence: 99%